Psychology and socioculture affect injury risk, response, and recovery in high-intensity athletes: a consensus statement - Wiese-Bjornstal, D. M. (Scandinavian Journal of Medicine & Science in Sports, 2010)
This consensus statement summarizes key contemporary research themes relevant to understanding the psychology and socioculture of sport injury. Special consideration is given toward high-intensity sport in which elite athlete training and performance efforts are characterized by explosive physical speed and strength, mental fortitude to push physical limits, and maximum effort and commitment to highly challenging goals associated with achieving exceptional performance. Sport injury occurrence in high-intensity sport is an adverse and stressful health event associated with a complex multitude of risks, consequences and outcomes. A biopsychosocial (Engel, 1980) view is advocated which contextualizes an understanding of the psychological aspects of sport injury in light of influential sociocultural, ethical, and biomedical issues. Outcomes related to athlete health and performance excellence are of equal importance in considering how psychological scholarship, expertise and services can be used to improve efforts focused on the prevention and management of sport injury among high-intensity athletes. The consensus view is that psychology and socioculture do affect sport injury risk, response and recovery in high-intensity athletes, and that continued efforts in psychological research and professional practice are needed to protect athlete physical and mental health and contribute toward performance excellence and career longevity.